Vitamin K status, supplementation and vascular disease: a systematic review and meta-analysis. Issue 12 (4th December 2018) - Lees, Jennifer Susan; Chapman, Fiona A; Witham, Miles D; Jardine, Alan G; Mark, Patrick B
Abstract : Objectives: Vascular stiffness (VS) and vascular calcification (VC) are surrogate markers of vascular health associated with cardiovascular events. Vitamin K-dependent proteins (VKDP) are associated with VS and VC and require vitamin K for activity. We conducted a systematic review and meta-analysis of: (1) the effect of vitamin K supplementation on VS and VC and (2) association of inactive VKDP levels with incident cardiovascular disease and mortality. Methods: Two authors searched MEDLINE and Embase databases and Cochrane and ISRCTN registries for studies of vitamin K clinical trials that measured effects on VC, VS or VKDP and longitudinal studies assessing effect of VKDP on incident CVD or mortality. Random effects meta-analyses were performed. Results: Thirteen controlled clinical trials (n=2162) and 14 longitudinal studies (n=10 726) met prespecified inclusion criteria. Vitamin K supplementation was associated with significant reduction in VC (−9.1% (95% CI −17.7 to −0.5); p=0.04) and VKDP (desphospho-uncarboxylated matrix Gla protein; −44.7% (95% CI −65.1 to −24.3), p<0.0001) and uncarboxylated osteocalcin; −12.0% (95% CI −16.7 to −7.2), p<0.0001) compared with control, with a non-significant improvement in VS. In longitudinal studies with median follow-up of 7.8 (IQR 4.9–11.3) years, VKDP levels were associated with a combined endpoint of CVD or mortality (HR 0.45 (95% CI 0.07 to 0.83), p=0.02). Conclusions: Supplementation with vitamin K significantly reduced VC, but not VS, compared with control. The conclusions drawn are limited by small numbers of studies with substantial heterogeneity. VKDP was associated with combined endpoint of CVD or mortality. Larger clinical trials of effect of vitamin K supplementation to improve VC, VS and long-term cardiovascular health are warranted. Trial registration number: CRD42017060344.